Study of cone and seed characteristics of Pinus sibirica in difference between Khangai and Khentii mountains - Ariunbaatar, Tumurbaatar; Temuujin, Byambaa; Lyankhua, Bayasgalankhuu (Mongolian Journal of Botany, 2023)
Pinus sibirica is spread over 612.7 thousand hectares or 5.2 percent of the 13.8 million hectares of forest areas in the northern part of Mongolia between 68˚30`and 46˚30` north latitude. The forest with Cedar is important effective for surface water runoff, and protects soil from erosion, increases river flow, improves climate, absorbs carbon through plant photosynthesis, creates a habitat for animals, plants, and microorganisms, and maintains permafrost, emits phytoncides and cleans the air. In our research, 12 sample plots of Cedar forests of Khangai and Khentii mountains were established and 6 parameters of general characteristics of cones and seeds were compared. Therefore, the indicator of the Cedar cone in the Khangai mountains are higher than in the Khentii mountains. Conversely, the number of seeds and scales in one cone of Khentii mountains are higher than the Khangai mountains. 1000 seed weight and number of scales in Cedar cones are inversely related to geographic location, and the width of the cones is positively and directly related to the fact that could be that the altitude of Khentii mountains is 1400-1700m from above sea level, and the Cedar of the Khangai mountains grows at an average height if 2000m from above sea level. Хангай, Хэнтийн нурууны Сибирь хушны боргоцой болон үрийн зарим үзүүлэлтүүдийн ялгаа Хураангуй. Сибирь хуш нь Монгол орны хойт өргөргийн 68°30’ -аас 46°30’-ын хооронд умард хэсгийн ой бүхий талбай 13.8 сая га байгаагийн 5.2 хувь буюу 612.7 мянган га талбайд тархан ургадаг. Хушин ой нь хөрсний гадаргын усны урсацыг шингээж, хөрсийг элэгдэл эвдрэлээс хамгаалах, гол мөрний усны урсацыг нэмэгдүүлэх, уур амьсгалыг зөөлрүүлэх, ургамлын фотосинтезээр нүүрстөрөгчийг нөөцлөх, амьтан, ургамал, бичил биетний амьдрах орчныг бүрдүүлэх, мөнх цэвдгийг тогтоон барих, фитонцид ялгаруулж, агаар цэвэршүүлэх зэрэг экологид чухал үүрэг гүйцэтгэдэг. Бидний судалгаагаар Хангай, Хэнтийн нурууны хушны ой бүхий 12 дээж талбай байгуулан боргоцой болон үрийн ерөнхий шинж бүхий 6 үзүүлэлтийг харьцуулан үзэхэд Хангайн нурууны хушны боргоцойн үзүүлэлтүүд Хэнтийн нуруунаас өндөр байна. Харин Хэнтийн нурууны хушны нэг боргоцойн дахь үрийн тоо болон хайрсны тоо нь Хангайн нурууны дээжнээс өндөр байна. Хушны боргоцойн 1000 үрийн жин болон хайрсны тоо нь газарзүйн байршлаас урвуу сул хамааралтай, боргоцойн өргөн нь эерэг шууд хамааралтай байгаа нь Хэнтийн нурууны д.т.д өндөршил нь 1400-1700 м бол, Хангайн нурууны хуш нь дунджаар 2000 м өндөрт тархан ургаж байгаатай холбоотой байж болох юм. Түлхүүр үгс: Сибирь хуш, Хангай, Хэнтийн нуруу, боргоцойн урт, өргөн, 1000 үрийн жин